Aporte del aviturismo en el desarrollo turístico sostenible en el Sector Puerto Bajaña del Cantón Buena Fe, año 2019 - Hurtado Delgado, Joselyn Adriana (2020)
The following research work is based on the theme "CONTRIBUTION OF AVITURISM IN THE SUSTAINABLE TOURISM DEVELOPMENT OF THE PUERTO BAJAÑA CANTÓN BUENA FE SECTOR, YEAR 2019" obtaining as the promotional purpose of bird watching to collaborate with sustainable tourism development. This research work is divided into chapters which are detailed as follows: CHAPTER I: The topic is presented, it is discussed in context of the topic at the international, national, local and institutional level based on criteria of various authors, it can also be seen that the problem is discussed, about the delimitation, the objectives of the research and justification of the work done. CHAPTER II: It is based on the criteria of several authors and bibliographies taken from various sources, the variables of the subject, continuing with the background, category of analysis, theoretical position to get through this to the personal criteria on the hypotheses and variables extracted. CHAPTER III: The tabulation of data from the surveys carried out to the inhabitants of the Buena Fe canton is obtained, where through tables and graphs a better intuition of the answers obtained is given and thus this way it is concluded and recommended to clarify the Responses of respondents and what can be done to improve the problem. CHAPTER IV: In this chapter, the proposal and what is going to be carried out based on the surveys and opinions of the inhabitants will be made known for improvement, make a diagnosis, analysis and prevail the responses to continue step by step with the proposed, information on the purpose of this research to collaborate in the sustainable tourism development and promotion of bird watching.